Symptomatic Bradycardia Due to Alectinib in a Patient with Advanced Stage of NSCLC - Ceva Wicaksono Pitoyo; Cleopas Martin Rumende; Anindita Kartika Wiraputri; Fatira Ratri Audita (Acta Medica Indonesiana)
Alectinib is one of the targeted therapies commonly given to patients with advanced non-small cell lung cancer (NSCLC) with mutations in the ALK gene. The most common adverse effects of alectinib are fatigue, constipation, edema, myalgia and anemia. Meanwhile, bradycardia was reported as a very common adverse effect, but generally asymptomatic, unlike the reported patient in this case report. This case report’s purpose is to increase awareness of the possibility of adverse effects due to alectinib administration that require immediate intervention in order to improve the quality of life and patient survival, especially in patients with advanced NSCLC.